Operators and their human–robot interdependencies: implications of distinct job decision latitudes for sustainable work and high performance - Wolffgramm, Milan R.; Corporaal, Stephan; Groen, Aard J. (Frontiers in Robotics and AI, 2025)
The collaborative robot (cobot) has the potential to remove barriers for individual operators when deciding on the deployment of robotics in their work. Ideally, using their opportunities to (re)design work (i.e., job decision latitudes), the operator establishes synergetic human–cobot interdependencies that enable the human–cobot production unit to achieve superior performance and foster more sustainable work perceptions than manual production units. However, it remains scientifically unclear whether the operator is both willing to and capable of using cobot-related job decision latitudes, what this means for designing human–cobot interdependencies, and whether these designs improve unit outcomes. Therefore, we built a manual and three human–cobot production units with distinct job decision latitudes. Forty students participated in the manual production unit and operated one of the human–cobot production units during an assembly simulation. Sophistically accounting for individual differences, the results illustrated that most operators used speed- and task-related job decision latitudes to design their human–cobot interdependencies. These behaviours often led to increased productivity and more motivating working conditions. At the same time, these human–cobot interdependencies frequently resulted in limited human–robot interactions, poor production reliability, and more psychological safety risks. This contribution lays a rich foundation for future research on involving individual operators in developing modern production systems.